Learning to search. The importance of eye movements in the decrease of response times during a visual choice reaction time task - Aleksandra Kroll; Monika Mak; Jerzy Samochowiec (Journal of Eye Movement Research)
Reaction times are often used as an indicator of the efficiency of the processes in the central nervous system. While extensive research has been conducted on the possible response time correlates, the role of eye movements in visual tasks is yet unclear. Here we report data to support the role of eye movements during visual choice reaction time training. Participant performance, reaction times, and total session duration improved. Eyemovements showed expected changes in saccade amplitude and resulted in improvement in visual target searching.